Cost–benefit analysis of controlling rabies: prioritizing areas in rural setting of Maner: a cross sectional study - Prasad, Nidhi; Kumar, Binay; Chaudhary, Sanjay Kumar; Kumar, Sanjay (International Journal Of Community Medicine And Public Health, 2019)
Background: Rabies being a preventable disease with no treatment available once onset starts but can be easily prevented by post-exposure among all animal bite victims. So it is essential to take the full course of vaccination for complete protection. Methods: The present study was a hospital based cross sectional study and was carried out in rural health training centre in Maner, Patna. Results: Our study included 340 patients who attended anti rabies clinic for post exposure prophylaxis. Among them 65% were children (<15 years) comprising mostly males (69%) and mostly of category III exposure. Direct cost of post exposure vaccination when compared with the cost of pre exposure prophylaxis is one-third (approx). Conclusions: Compliance to anti-rabies vaccination for post-exposure prophylaxis is still low and they are still at risk of developing rabies. Reasons being irregular supply of vaccine and immunoglobulin in government hospitals, loss of wages, forgotten dates, cost incurred to buy from outside and distance from the hospital if referred to other centre. Seeing the current scenario, planning and prioritizing areas to achieve our goal and lessen economic burden is need of the hour. We infer that pre exposure prophylaxis may be a cost effective strategy which can aid in the control and elimination of rabies in endemic settings.